Immunoassays of chemically modified polysaccharides, glycans in glycoproteins and ribose in nucleic acids - Strmečki, Slađana; Trefulka, Mojmír; Zatloukalová, Pavlína; Durech, Michal; Vojtesek, Borivoj; Paleček, Emil (Analytica chimica acta, 2017)
Glycosylation of proteins plays an important role in health and diseases. At present new simple and inexpensive methods of glycoprotein analysis are sought. We developed a monoclonal antibody Manost 2.1 in mice after immunization with the adduct of mannan with Os(VI)temed complex (temed is N,N,N',N'-tetramethylethylenediamine). The specificity of this antibody to different biomolecules treated with Os(VI)temed was tested using dot blot immunoassay. Manost 2.1 showed specificity toward Os(VI)temed-modified polysaccharides, glycoproteins and ribonucleotide at the 3'-end in DNA. The antibody recognized neither the unmodified compounds nor the non-glycosylated proteins treated with Os(VI)temed. We also performed western blotting and Coomassie silver blue staining of mixtures of biomacromolecules treated with Os(VI)temed and identified specifically the modified glycoproteins. The immunochemical method using Manost 2.1 was compared with electrochemical analyses based on redox signals of the Os(VI)temed adducts, with similar results in terms of sensitivity. This new antibody-based approach opens the door for rapid and inexpensive analysis of glycans and glycoproteins in various scientific and medical fields, including cancer research and the future application of glycoprotein detection in clinical practice.
Keywords: Glycoproteins; imunoanalýza; Antibody against chemically modified carbohydrates; Carbon and mercury electrodes; polysacharidy; nukleové kyseliny; DNA; Immunoassay; monoklonální protilátky; Os(VI) complexes; Antibodies, Monoclonal; Mice; Ribose; zvířata; Glycoprotein adduct immunoassays; Voltammetry of chemically modified glycoproteins; myši; ribosa; Nucleic Acids; glykoproteiny; Polysaccharides; Carbohydrate chemical modification; Animals